The role of mitochondria-related key genes in primary biliary cholangitis was analyzed based on transcriptome sequencing data - Tao, Yanping; Zhong, Lei; Shen, Qihua; Zhang, Xiaofan; Xu, Xuyun; Feng, Runlin (Frontiers in Immunology, 2025)
IntroductionMitochondrial dysfunction is implicated in the pathogenesis of primary biliary cholangitis (PBC), but the roles of mitochondria-related genes (MRGs) remain unclear. We aimed to identify key MRGs associated with PBC and validate their expression at transcriptional and protein levels.MethodsPeripheral blood from PBC patients and healthy controls underwent RNA-seq. MRGs were sourced from MitoCarta 3.0. After quality control, differentially expressed genes were defined between PBC and controls and integrated with weighted gene co -expression network analysis to obtain candidate genes. LASSO and SVM-RFE selected hub genes, whose diagnostic performance was assessed by ROC in both the discovery cohort and an external validation dataset. Functional enrichment, immune-cell composition analyses, and regulatory network construction (miRNA/lncRNA/TF) were performed. Protein and mRNA expression were validated by liver -tissue immunohistochemistry and peripheral-blood RT-qPCR, respectively. Disease correlation and drug-prediction analyses were conducted.ResultsSHANK2 and TGM2 were identified as hub MRGs, showed higher expression in PBC, and achieved AUC values >0.7. Enrichment linked SHANK2 to Bcell receptor, T-cell receptor, and Wnt signaling pathways, while TGM2 associated with oxidative phosphorylation and nucleotide metabolism. Immune-cell profiles differed between PBC and controls, and selected cell types correlated with hub-gene expression. Regulatory analyses suggested modulation of SHANK2 and TGM2 by molecules including SLFN12L and DNAH10OS. Immunohistochemistry revealed elevated, stage-associated protein expression of both genes in PBC liver tissues, and RT-qPCR confirmed higher peripheralblood mRNA levels. Drug/disease analyses indicated therapeutic potential for targeting these genes.DiscussionSHANK2 and TGM2 emerge as key MRGs linking mitochondrial dysfunction with immune dysregulation in PBC and may serve as diagnostic biomarkers and therapeutic targets; further mechanistic and clinical validation is warranted.